2018
DOI: 10.1371/journal.pone.0206670
|View full text |Cite
|
Sign up to set email alerts
|

Tucum-do-cerrado (Bactris setosa Mart.) modulates oxidative stress, inflammation, and apoptosis-related proteins in rats treated with azoxymethane

Abstract: Oxidative and inflammatory responses play an important role in the development and prevention of cancer, with both responses being modulated by phytochemical compounds. This study investigated the chemopreventive effect of tucum-do-cerrado fruit in rats treated with azoxymethane. Wistar rats were treated for 12 weeks with: a control diet (CT); a control diet + AOM (CT/DR); a control diet + 15% tucum-do-cerrado (TU); or a control diet + 15% tucum-do-cerrado + AOM (TU/DR). The association of tucum-do-cerrado and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
1
0
2
Order By: Relevance
“…Among the species of this genus, B. setosa is the one with the widest distribution (Fernandes, 1995), which justifies the greater number of studies found for this species. Currently, studies have been carried out mainly with the chemical characterization of its fruits due to their high antioxidant activity (Boeing et al, 2017; Campos et al, 2018; Rosa et al, 2016). Even with several potentials to be investigated, no study has been carried out in areas such as genetics, physiology and tissue culture; topics that we recommend for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the species of this genus, B. setosa is the one with the widest distribution (Fernandes, 1995), which justifies the greater number of studies found for this species. Currently, studies have been carried out mainly with the chemical characterization of its fruits due to their high antioxidant activity (Boeing et al, 2017; Campos et al, 2018; Rosa et al, 2016). Even with several potentials to be investigated, no study has been carried out in areas such as genetics, physiology and tissue culture; topics that we recommend for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as espécies desse gênero, B. setosa é a que apresenta maior distribuição (Fernandes, 1995), o que justifica o maior número de estudos encontrados para essa espécie. Atualmente, os estudos têm sido realizados principalmente na caracterização química de seus frutos devido à sua alta atividade antioxidante (Boeing et al, 2017; Campos et al, 2018; Rosa et al, 2016). Mesmo com vários potenciais a serem investigados, nenhum estudo foi realizado em áreas como genética, fisiologia e cultura de tecidos; tópicos que recomendamos para estudos futuros.…”
Section: Discussionunclassified
“…Portanto, os fitoquímicos, indutores da via de transcrição Nrf2, exercem efeitos quimiopreventivo favoráveis, por meio de diferentes mecanismos antioxidantes, podendo contribuir para a redução da formação de tumores após a diminuição dos níveis de ERO. Essas ações protegem a célula contra danos oxidativos e inflamatórios, que podem desencadear um possível processo cancerígeno 50 .…”
Section: -11unclassified